Effects of The Application of Logic Gate Simulator Media in Improving The Results and Learning Activities of XI Grade Vocational High School Students - Nur, Akmal; Herpratiwi, Herpratiwi; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This literature review evaluates 12 previous studies on the use of simulation software in learning digital electronics and logic gates, with the aim of analysing its impact on student learning outcomes and activities. Various simulation software such as Proteus, Logisim, Circuit Wizard, and others are used to improve students' understanding of complex concepts, practical skills, and motivation in the subjects of electronics and digital logic. The results show that simulation software effectively improves student learning outcomes, engagement, and motivation by providing practical and interactive experiences without the need for expensive physical components. However, challenges such as limited access to the required hardware and the need for proper teacher training were also highlighted. Despite these challenges, this study shows that simulation software is a promising tool for improving the quality of electronics and digital logic learning if it is properly implemented and supported by adequate infrastructure.